Coherent transfer between low-angular-momentum and circular Rydberg states - Signoles, Adrien; Dietsche, E. K.; Facon, A.; Grosso, D.; Haroche, S.; Raimond, J. M.; Brune, M.; Gleyzes, S. (Physical review letters, 2017)
We realize a coherent transfer between a laser-accessible low-angular-momentum Rydberg state and the circular Rydberg level with maximal angular momentum. It is induced by a radio frequency field with a high-purity σ+ polarization resonant on Stark transitions inside the hydrogenic Rydberg manifold. We observe over a few microseconds more than 20 coherent Rabi oscillations between the initial Rydberg state and the circular level. We characterize these many-Rydberg-level oscillations and find them in perfect agreement with a simple model. This coherent transfer opens the way to hybrid quantum gates bridging the gap between optical communication and quantum information manipulations with microwave cavity and circuit quantum electrodynamics.
Gesehen am 19.08.2019